2021
DOI: 10.3892/or.2021.8159
|View full text |Cite
|
Sign up to set email alerts
|

Role of reactive oxygen species in tumors based on the ‘seed and soil’ theory: A complex interaction (Review)

Abstract: Tumor microenvironment (TME) can serve as the 'soil' for the growth and survival of tumor cells and function synergically with tumor cells to mediate tumor progression and therapeutic resistance. Reactive oxygen species (ROS) is somewhat of a double-edged sword for tumors. Accumulating evidence has reported that regulating ROS levels can serve an anti-tumor role in the TME, including the promotion of cancer cell apoptosis, inhibition of angiogenesis, preventing immune escape, manipulating tumor metabolic reorg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 207 publications
(276 reference statements)
0
9
0
Order By: Relevance
“…ROS maintenance to a certain level is necessary and required for cellular proliferation and survival [38]. On the other hand, the rise in ROS can promote cancer cell death, inhibit cancer cell angiogenesis, and prevents immune escape in TME [39]. In this study, PFPE increased MDA levels compared to control and vehicle groups.…”
Section: Discussionmentioning
confidence: 51%
“…ROS maintenance to a certain level is necessary and required for cellular proliferation and survival [38]. On the other hand, the rise in ROS can promote cancer cell death, inhibit cancer cell angiogenesis, and prevents immune escape in TME [39]. In this study, PFPE increased MDA levels compared to control and vehicle groups.…”
Section: Discussionmentioning
confidence: 51%
“…A moderate increase in ROS levels has been shown to promote pro-tumorigenic signaling, enhance tumor development and progression, drive DNA damage and genome instability, and modulate drug resistance [34] , [37] . However, ROS are also capable of triggering programmed cell death by activating signaling pathways and modulation of oxidative stress is considered as an anticancer strategy [34] , [37] , [38] , [39] . As different susceptibility to cell death was documented in three OS cell lines ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, manipulating intracellular redox status of cancer cells seems to be an attractive and promising approach for cancer therapy. However, studies have shown that some pro-oxidant therapies also promote ROS-induced drug resistance [ 181 , 182 ]. Possible causes may include lipid peroxidation during OS induced by chemotherapy drugs.…”
Section: The Adverse Effects Of Drug-induced Oxidative Stress In Canc...mentioning
confidence: 99%